The development of water tube media nature theme to improve soft skills and early childhood language - Avriani, Indira Olan; Hasibuan, Rachma; Trihariastuti, Retno (Universitas Malikussaleh, 2022)
The purpose of the research is to analyze the feasibility and effectiveness of the Water Tube Media have developed soft motor skills and early childhood language in group A Bina Prestasi Surabaya Kindergarten. The research uses the Dick & Carey research and development model. The result of the research is water tube media products to develop soft motoric skills and early childhood language. The development of the media includes material is the introduction about water characteristics. The study was conducted in class A1 at TK Bina Prestasi Surabaya. Based on the formative test to experts and children obtained qualitative and quantitative data, qualitative data are suggestions from experts and quantitative data in the form of a percentage of child observation sheets. From the percentage of assessment of formative tests experts and also children, the water tube media is feasible and effective to be used in learning to develop soft skills and early childhood language.